A new strategy for de-oxidation of diamond-wire sawing silicon waste via the synergistic effect of magnesium thermal reduction and hydrochloric acid leaching. (1st September 2022) - Yang, Fan; Yu, Wenzhou; Rao, Zitao; Wei, Peng; Jiang, Weiyan; Chen, Hao
Abstract: With the rapid development of photovoltaic industry, the amount of diamond-wire sawing silicon waste (DWSSW) increased dramatically. Recently, how to achieve cost-effective deoxygenation of DWSSW should be the most critical issue in silicon waste recycling. Herein, a new strategy for de-oxidation from DWSSW, employing Mg vapor as de-oxidation agent and hydrochloric acid (HCl) as leaching agent, under low temperature was suggested. The de-oxidation mechanism and the mineralogical evolution of different phases during the magnesium thermal reduction and acid leaching were clarified. Results showed that the impurity oxygen in DWSSW exists as amorphous SiO2 on the surface of Si particles, which can be eliminated by transforming it into crystalline MgO using magnesium thermal reduction and followed by acid leaching. As the reduction condition was controlled at 1333 K for 2 h, the residual oxygen content in DWSSW was 0.9643% and the de-oxidation fraction attained 93%. Additionally, the removal rate of impurities Al and Fe were 99.06% and 92.20%, respectively, and the Si recovery rate achieved 88%. Taking into consideration the recoverability of Mg, the cost of the process will be reduced significantly, making this process more viable in industry. Graphical abstract: Image 1 Highlights: A process of de-oxidation for diamond-wire sawing silicon waste was proposed. Mechanism of de-oxidation for silicon waste via magnesium thermal reduction was clarified. The residual oxygen in Si and de-oxidation fraction was 0.9643 wt% and 93%, respectively. The recovery rate of diamond-wire sawing silicon waste can achieve 88% in the laboratory.